2021
DOI: 10.18196/ftl.v6i1.10174
|View full text |Cite
|
Sign up to set email alerts
|

Word Recognition and Reading Skills to Improve Reading Comprehension

Abstract: This research aimed at showing the influence of word recognition, and using skimming and scanning skills to improve reading comprehension. Participants were a group of 15 students whose ages ranged from 14 to 16. They had problems in reading comprehension and vocabulary.  This action research was conducted at a private language institute. The instruments to collect data were pre- and post-surveys, pre- post-tests, learning logs, skimming and scanning forms, and an interview. They provided quantitative and qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…e data suggest that word recognition activities and fluency training improved the reading comprehension of Iranian EFL students. is is consistent with a significant body of research that has found that word recognition and fluency training improve reading comprehension (e.g., [9,54,58,68,74,84,89,90,[93][94][95][96][97][98]). However, Ribeiro et al (2016) had argued that reading fluency is the strongest predictor of reading comprehension, but this experiment provided evidence that fluency in reading is by no means a better practice than word recognition activities, at least at the preintermediate level of language proficiency.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…e data suggest that word recognition activities and fluency training improved the reading comprehension of Iranian EFL students. is is consistent with a significant body of research that has found that word recognition and fluency training improve reading comprehension (e.g., [9,54,58,68,74,84,89,90,[93][94][95][96][97][98]). However, Ribeiro et al (2016) had argued that reading fluency is the strongest predictor of reading comprehension, but this experiment provided evidence that fluency in reading is by no means a better practice than word recognition activities, at least at the preintermediate level of language proficiency.…”
Section: Discussionsupporting
confidence: 88%
“…Reading is regarded as a stepby-step process promoting the development of higher-order thinking abilities [9,39]. Decoding, comprehending, analyzing, and integrating the full concept of a passage are the main parts of reading [40,41].…”
Section: Eoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that vocabulary is an important component of language, one cannot ignore the importance of the position of vocabulary in the four language skills [23]. Starting from the importance of vocabulary in language learning motivates Arabic language teachers to teach vocabulary and introduce it early [22], as well as practice it in the language process [24].…”
Section: Morphology and Its Teaching Solutionmentioning
confidence: 99%
“…According to the research data, the effect size of the application of the Think-Pair-Share strategy on students' reading skills in English teaching and learning is also in the high category with 1.67. Karademir and Ulucinar in Chamba and Avila (2021) considered reading as a step-by-step line of action with basic elements such as decoding the message, conceiving the message, analyzing it, and integrating the whole idea the text. The think-Pair-Share strategy actively encourages and motivate students in thinking, exploring, and sharing their opinion and ideas from reading activities.…”
Section: The Influence Of Think-pair-share Strategy Based On Regionmentioning
confidence: 99%